ANALISIS TINGKAT ASUPAN KALSIUM DAN VITAMIN D TERHADAP KEJADIAN STUNTING PADA BALITA DI SIJUNJUNG - Elsa Marsellinda; Siska Ferilda (Jurnal Buana Farma, 2023)
The problem of stunting is one of the nutrition problems that the Indonesian government focuses on. Calcium and vitamin D are nutrients that affect bone mineralization. Good bone mineralization during growth allows optimal linear growth. This study aims to determine the relationship between calcium and vitamin D intake in stunted and non-stunted children aged 12-59 months in Sijunjung Regency. This research method is analytic observational with cross sectional design. The research sample was children aged 12-59 months. Data analysis methods using the SPSS program. Based on the results of the study obtained based on age group, the highest stunting at the age of 24-35 months 57.14% and the lowest in the age group 48-59 months 7.14%. then the age group is not stunted, namely the age of 24- 35 months 45.45% and the lowest in the age group 48-59 months 9.09%. Based on food intake containing high calcium and vitamin D, the category is less, namely 50.00% of stunted children and 13.64% of non-stunted children, for food intake containing low calcium and vitamin D, the category is high in both stunted and non-stunted children. Based on statistical tests, there is an effect of the level of food intake containing calcium and vitamin D on the incidence of stunting (p<0.05). Based on the results of the study, it can be concluded that calcium and vitamin D intake affect the incidence of stunting in toddlers in Sijunjung.